Visual marketing : 99 proven ways for small businesses to market with images and design - Langton, David, 1961- (Wiley, 2011)
"Effective creative strategies for business owners or marketersWhether it's on the web, in a book, or live in-person, the most effective solutions are those that unexpectedly grab our attention. David Langton and Anita Campbell identify eye-catching and thought-provoking marketing and PR tips, ideas, and stunts. In this compendium of winning ideas will inspire small business leaders, creative professionals, and students. Award-winning visual communication designer David Langton has worked for a range of businesses from Fortune 500 leaders to mom and pops. Anita Campbell, an internationally known small business expert, reaches over 1 million small business owners and stakeholders annually. Through case studies, photos, and illustrations, Visual Marketing displays creative marketing campaigns that brought attention to small businesses in unique, compelling, and unexpected ways. Online visual marketing solutions may include apps, interactive games tools and modules; infographics; HTML emails / e-newsletters; widgets; YouTube videos; flash animation; social networking campaigns; websites, weblets, mini-sites; blogs; podcasts / MP3s; projected signage; PowerPoint / keynote presentations In print solutions may include brochures, flyers; annual reports; books; direct mail, post cards; newsletters; invitations; letters; press releases; infographics On-site, giveaways, exhibit, and tradeshow solutions may include live events and performances; signs; billboards; exhibits; banners; tent cards; posters; plasmas screens; kiosks; giveaways: tchotchkes, t-shirts, tote bags, etc.; floor graphics/vinyl graphic wraps With Visual Marketing, you'll discover 99 powerful strategies for capturing the attention of your potential customers"--